Pengaruh Belanja Modal Terhadap Distribusi Pendapatan (Bukti Data Panel Kabupaten Kota di Aceh) - Raudhatul Anzira; Rana Maulida; Bulan Bidadari; Eko Fathul Haqiqi; T. Muhammad Danil; Khairul Amri (Jurnal Ekonomi Manajemen dan Sekretari, 2023)
The main purpose of our research study is to investigate the effect of capital expenditure provided by the government to generate regional income. Using a panel dataset from 23 districts / cities in Aceh province from 2015 to 2017. The permanent effect method The panel panel regression method of the fixed effect method and the Granger causality test was operationalized to test the functional relationship between these variables. The study found that the level of capital expenditure was not significant for income distribution in Aceh. This indicates that the economic activity of the people in the area is highly dependent on the availability of capital expenditure budget allocations, regions with a relatively larger portion of capital expenditure are able to generate income that is also relatively larger compared to regions with relatively smaller capital expenditure. Therefore, the Government of Aceh's regencies in Aceh needs to increase the allocation of regional budgets in the form of capital expenditure. As well as the central, provincial and district governments in Aceh must pay serious attention to capital expenditures given to all municipal districts in the area.